Feeding Patterns and Stunting among Toddlers in Tanjung Karangan Village - Larasati, Elta; Sari, Desri Maulina; Utama, Feranita; Yuliana, Indah (Universitas Nusa Cendana, 2023)
. The UNICEF report states that the prevalence of stunting in children under the age of five (toddlers) in 2019 reached 21.3%. Toddlers are active consumers where they can choose the food they like. Parenting patterns of feeding toddlers play an important role in their growth and development, because they are closely related to the health and intelligence of children. Inappropriate feeding parenting will have an impact on nutritional deficits so that it will trigger stunting. The purpose of this study was to determine the relationship between feeding parenting and the incidence of stunting. This study is a quantitative study with a cross-sectional research design. Respondents were 48 people, who were selected by purposive sampling technique. The data were processed by statistical tests and analyzed descriptively. The results showed that there were 22.9% of respondents experiencing stunting and most of the respondents had a feeding pattern in the right category (79.2%). The results of the analysis stated that the parenting style of feeding (p < 0.001), family income (p = 0.015), and the mother's last education (p = 0.001) were related to the incidence of stunting. The conclusion of this study is that feeding parenting in the inappropriate category has a risk of stunting 38 times compared to toddlers who are given feeding parenting in the appropriate category (PR = 38,000, 95% CI: 5,494 – 262,851). The results of this study are expected to be an evaluation for parents so that they can pay attention to feeding parenting patterns so that children can grow and develop according to their age stages.